Hungry girl clean & hungry : obsessed! : all-natural recipes for the foods you can't live without - Lillien, Lisa (St. Martin's Griffin, 2017)
Lisa Lillien has sold millions of books by serving up clever and deliciously easy recipes with low calorie counts, huge portions, and easy-to-find ingredients that are good for you. With eleven New York Times bestsellers under her belt, Lisa is taking things to the next level with Hungry Girl Clean & Hungry OBSESSED! Keeping in line with the current clean-eating food trend (and as a follow-up to her to last smash-hit book, Hungry Girl Clean & Hungry), she's taking on the beloved foods that Americans are OBSESSED with--comfort foods, junk foods, international favorites, desserts, and more! Donuts, lasagna, fried chicken, quesadillas, fudge... No food is off-limits, and all of them have been completely re-created, re-vamped, and CLEANED UP! With the unique and healthy recipes in this cookbook, you can finally enjoy ALL the foods you crave while eating clean and staying lean!